Methylation profiling identifies two subclasses of squamous cell carcinoma related to distinct cells of origin - Rodríguez Paredes, Manuel; Lucena Porcel, Carlota; Feuerbach, Lars; Brors, Benedikt; Herpel, Esther; Hofmann, Thomas G.; Lyko, Frank (Nature Communications, 2018)
Cutaneous squamous cell carcinoma (cSCC) is a skin cancer that normally progresses from UV-induced actinic keratosis (AK). Here, the authors investigate the epigenomics of cSCC and highlight two distinct subclasses of AK and cSCC originating from distinct keratinocyte differentiation stages.
Gesehen am 14.04.2020